2023
DOI: 10.1108/jarhe-09-2023-0426
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the opportunities and challenges of artificial intelligence in higher education: a qualitative study

Fateme Jafari,
Ahmad Keykha

Abstract: PurposeThis research was developed to identify artificial intelligence (AI) opportunities and challenges in higher education.Design/methodology/approachThis qualitative research was developed using the six-step thematic analysis method (Braun and Clark, 2006). Participants in this study were AI PhD students from Tehran University in 2022–2023. Purposive sampling was used to select the participants; a total of 15 AI PhD students, who were experts in this field, were selected and interviews were conducted.Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Although diverse, several of the studies included in this review are exploratory and experimental (Farazouli et al, 2023;Hallal et al, 2023;Jafari & Keykha, 2023;Khosravi et al, 2023), using expert validation techniques to examine the quality of chatbot responses to authentic examination questions that could be asked to students. We also observe that the majority of studies are either observational nature or based on small data sets, or is self-reported and as such cannot be yet used to identify robust ndings or generalizations for university teachers and their practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although diverse, several of the studies included in this review are exploratory and experimental (Farazouli et al, 2023;Hallal et al, 2023;Jafari & Keykha, 2023;Khosravi et al, 2023), using expert validation techniques to examine the quality of chatbot responses to authentic examination questions that could be asked to students. We also observe that the majority of studies are either observational nature or based on small data sets, or is self-reported and as such cannot be yet used to identify robust ndings or generalizations for university teachers and their practices.…”
Section: Discussionmentioning
confidence: 99%
“…We also found the discourse of altering authority re ected in the corpus. Several studies seem to align with this discourse about the integration of AI in education, such as in Dakakni and Safa, (2023) and Jafari and Keykha (2023), where the authors refer to AI learning systems as bene cial for students' convenience and personalised learning without the intervention of teachers. Additionally, Rodway and Schepman (2023) and Mohamed et al (2023), discuss AI in education as enabling teachers to offer individualised and 'customized' experiences to students.…”
Section: State Of the Evidencementioning
confidence: 92%
“…This nuance is echoed in the works of García-Peñalvo (2023) and Muñoz et al ( 2024), who argue that AI's effectiveness hinges on thoughtful design and implementation, emphasizing the need for AI to complement rather than replicate traditional pedagogical methods. The call for employing qualitative research methodologies, as Jafari & Keykha (2023) suggest, becomes imperative to capture the depth of students' interactions with AI technologies and their resultant learning experiences. Moreover, the potential for both positive and negative long-term effects of AI on education, highlighted by Pellas (2023), stresses the importance of conducting longitudinal studies.…”
Section: Intra-group and Inter-group Analysismentioning
confidence: 99%